2003
DOI: 10.1042/bst0311052
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and visualizing single molecular interactions in biology

Abstract: In recent years, considerable attention has focused upon the biological applications of the atomic force microscope (AFM), and in particular in its ability to explore biomolecular interaction events at the single molecule level. Such measurements can provide considerable advantages, as they remove the data averaging inherent in other biophysical/biochemical approaches that record measurements over large ensembles of molecules. To this end AFM has been used for both the high-resolution imaging of a range of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 51 publications
0
27
0
1
Order By: Relevance
“…More recently, surface roughness has also been implicated with β1 and β3-integrin mediated cell adhesion [28], as well as having a direct relationship with collagen synthesis [29]. In order to investigate the surface roughness of the Nafion and modified Nafion surfaces, Atomic Force Microscopy (AFM) was used [30]. Surfaces were prepared as specified above, and examined by an AFM (Molecular Imaging PicoScan, Pheonix, AZ).…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…More recently, surface roughness has also been implicated with β1 and β3-integrin mediated cell adhesion [28], as well as having a direct relationship with collagen synthesis [29]. In order to investigate the surface roughness of the Nafion and modified Nafion surfaces, Atomic Force Microscopy (AFM) was used [30]. Surfaces were prepared as specified above, and examined by an AFM (Molecular Imaging PicoScan, Pheonix, AZ).…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…When the tip approaches the surface (blue curve), the cantilever is first at rest and not deflected (1). When the tip touches the surface, the cantilever gets deflected upwards (2). During retraction (red curve), a ligandreceptor unbinding may be visible as a characteristic downwards nonlinear deflection of the cantilever (3), which reflects the stretching of the molecule crosslinkers.…”
Section: Ligand-receptor Interactionsmentioning
confidence: 97%
“…2). During the last 10 years, many different interactions of ligand-receptor complexes have been examined using the AFM [2,3,11,28,31,78]. These studies demonstrated that it was possible to detect and quantify ligand-receptor binding forces, typically in the range of 50-250 pN, and also to study the structural parameters that characterize ligand-receptor interactions.…”
Section: Ligand-receptor Interactionsmentioning
confidence: 98%
“…No primeiro grupo, o objetivo consiste em obter imagens da superfície da amostra para uma caracterização estrutural e dinâmica [22][23][24] . Em sistemas biológicos incluindo células, bactérias, vírus e biomoléculas, isso possibilita a compreensão dos fenômenos biofísicos/químicos envolvidos, constituindo-se em mais uma ferramenta auxiliar de análise e proporcionando um rápido desenvolvimento interdisciplinar [25][26][27][28][29][30][31][32] . Assim, é possí-vel se obter novas informações sobre as bases moleculares dos processos biológicos, como por ex., a investigação de biofilmes bacterianos com superfícies metálicas em sistemas industriais 33 , situações clínicas e adsorção de moléculas protéicas em superfí-cies de biomateriais 34 .…”
Section: Microscopia De Força Atômica (Afm)unclassified